Refractory hyperaldosteronism in heart failure is associated with plasma renin activity and angiotensinogen polymorphism. Issue 6 (June 2015) - Vergaro, Giuseppe; Fatini, Cinzia; Sticchi, Elena; Vassalle, Cristina; Gensini, Gianfranco; Ripoli, Andrea; Rossignol, Patrick; Passino, Claudio; Emdin, Michele; Abbate, Rosanna
Abstract : Aims: Refractory hyperaldosteronism is frequently observed in heart failure patients on up-to-date treatment, and holds prognostic value. Our aim was to identify which factors, either genetic or nongenetic, are associated with refractory hyperaldosteronism. Methods: We enrolled 109 consecutive patients with left ventricular systolic dysfunction [left ventricular ejection fraction (LVEF) 32 ± 10%; 86% males; age 65 ± 13 years (mean ± standard deviation)] on optimized adrenergic and renin-angiotensin-aldosterone system (RAAS) antagonism, undergoing clinical and neuroendocrine characterization, and genotyping for six polymorphisms in key RAAS-regulating genes [angiotensinogen (AGT M235T), angiotensin-converting enzyme (ACE-240A>T and I/D), angiotensin II type I receptor (AGTR1 1166A>C), aldosterone synthase (CYP11B2-344C>T) and renin (REN rs7539596)]. Results: Patients with refractory hyperaldosteronism ( n  = 41, 38%, with plasma concentration >180 ng/l, URL, median 283 ng/l, interquartile range 218–433), when compared with those without (106 ng/l, 74–144; P  < 0.001), were not different either for treatment or LVEF, while presented with different AGT M235T genotype distribution ( P  = 0.047). After adjustment for several humoral, instrumental, functional and therapeutical variables, only plasma renin activity (PRA) ( P  < 0.001) and potassium ( P  = 0.027) were independently associated with refractory hyperaldosteronism. Among polymorphisms, only AGT M235T ( P  = 0.038) was associated with refractory hyperaldosteronism, after adjustment for nongenetic variables. Conclusions: In conclusion, refractory hyperaldosteronism in heart failure may be influenced by AGT M235T polymorphism, among RAAS candidate genes, and by PRA, which may represent, respectively, a constitutive (genotype dependent) and a nongenetic (phenotype-dependent) trigger for aldosterone elevation. Abstract : Supplemental Digital Content is available in the text